Wilt disease suppression and yield enhancement in tomato (Lycopersicon esculentum) by application of Pseudomonas fluorescens-based biopesticide (Biofor-Pf) in Assam - Bora, L C; Deka, S N (The Indian Journal of Agricultural Sciences, 2007)
An experiment was conducted during 2003-05 to explore effective organic substrate-based biopesticide ’Biofor -Pf by using virulent cells of bacterial antagonist Pseudomonas fluorescens strain PfD-1. Three organic substrates, viz vermicompost, farmyard manure and mustard oil cake were compared for mass multiplication of the bacterial antagonist. Vermicompost-based biopesticide showed effective results in suppression of bacterial wilt (Ralstonia solanacearum Yabuchi et al.) incidence in tomato (Lycopersicon esculentum (L.) Mill.). Quantitative aspect of population dynamics of P.fluorescens at different days of storage was made to evaluate the shelf-life of the biopesticide and found that P.fluorescens maintained a steady population count up to 250 days of storage at room temperature. The biopesticide combination of vermicompost, P. fluorescens, carboxy methyl cellulose and mannitol showed best shelf life as it maintained highest population recovery at different days of storage. Application of this biopesticide with maximum shelf-life as combination of seed treatment, root application, soil application at transplanting and soil application at 30 days after transplanting showed minimum wilt incidence (8.83%), maximum yield (72 kg/plot) and highest population count (58.93 x 108cfu/ml) of P.,fluorescens in the tomato rhizosphere. A negative correlation between the population of P.fluorescens and per cent wilt incidence, between per cent wilt incidence and yield and a positive correlation between the population of P.fluorescens and the yield was recorded.